Symmetrical peripheral gangrene: Unusual complication of dengue fever - Patel, M. L. (Adv Biomed Res, 2016)
Symmetrical peripheral gangrene (SPG) is a rare clinical entity, infective, and noninfective both types of etiologies are responsible. The basic underlying pathology in SPG is being disseminated intravascular coagulation and carries a high mortality. Here, we describe a 52-year-old male with dengue fever, who developed bilateral symmetrical dry gangrene of both hand and feet. His dengue IgM antibody was positive. All the peripheral pulses of the affected limbs were palpable. Color Doppler study of upper and lower limb vessels showed normal flow. The patient was managed with intravenous fluids, low molecular weight heparin, and fresh frozen plasma. His general condition was improved within 72 h with no further progression of gangrene. Clinician should suspect the possibility of SPG while dealing a case of dengue fever presenting as peripheral gangrene.